EU Energy Security Strategy: The Impact Of The Russia-Ukraine War On The Energy Sector (2022-2024) - Tiara Lovysamina Zahir, Baiq; Saptatia Drajati Nugrahani, Henny; Sadadi, Puguh (International Journal of Educational Research & Social Sciences, 2024)
The Russia-Ukraine War of 2022 has prioritized energy security on the European policy agenda. This research aims to answer two critical questions in the aftermath of the 2022 Russian-Ukrainian War, such as what concrete steps were taken by the EU in response to the energy crisis triggered by the conflict, especially regarding reducing dependence on energy imports from Russia and how the EU's new energy policy after the 2022 Russian-Ukrainian War affected their efforts to reduce dependence on energy sources from Russia and stabilize energy supply in Europe. The analysis covers 2022 - 2024, using data from various sources such as official reports, literature reviews, and previous research. The research method includes a literature study using Barry Buzan's Regional Security Complexity Theory and Energy Security Concept, descriptive analysis to understand the EU's concrete steps in responding to the energy crisis, and comparative analysis to evaluate the impact of EU policies in reducing dependence on Russian energy. The analysis shows that the EU has taken strategic steps in dealing with the impact of the Russia-Ukraine war on energy security. In the context of gas supplies from Russia, although gas supplies will likely remain via pipeline and LNG to some EU Member States that do not apply strict sanctions even after 2027, the volume of these supplies is expected to decrease significantly.